Assessment of the Tumbling-Snake Model against linear and nonlinear rheological data of bidisperse polymer blends - Stephanou, Pavlos S.; Kröger, Martin (My University, 2019)
We have recently solved the tumbling-snake model for concentrated polymer solutions and entangled melts in the academic case of a monodisperse sample. Here, we extend these studies and provide the stationary solutions of the tumbling-snake model both analytically, for small shear rates, and via Brownian dynamics simulations, for a bidisperse sample over a wide range of shear rates and model parameters. We further show that the tumbling-snake model bears the necessary capacity to compare well with available linear and non-linear rheological data for bidisperse systems. This capacity is added to the already documented ability of the model to accurately predict the shear rheology of monodisperse systems.
Keywords: Stochastic differential equation; Polymer melt; Link tension coefficient; Entanglements; Bidisperse systems